Infrastructure and economic growth in ECOWAS member states: The Westerlund co-integration approach - Kabir Usman, Fadila; Zakaree, Saheed; Muktar, Mustapha; Yakubu, Alfa; Olure-Bank, Adeyinka (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This research explores the impact of infrastructure on member states' economic growth in the Economic Community of West African States (ECOWAS). Utilizing panel secondary data sourced from the World Bank Development Indicators (WDI) and the African Infrastructure Development Index (AIDI) across all fifteen ECOWAS Member States over eighteen years, the study employs the panel Non-linear Autoregressive Distributed Lag (NARDL) model and the Westerlund co-integration test for analysis. The findings reveal that investments in infrastructure, improvements in the African Development Index, and enhancements in the Electricity Composite Index significantly contribute to the economic growth of ECOWAS countries. Specifically, infrastructure investment is associated with a 0.01 per cent increase in the Gross Domestic Product (GDP) of the ECOWAS countries studied. In comparison, the African Development Index and the Electricity Composite Index are linked to increases in GDP by 0.292 per cent and 0.987 per cent, respectively, in the long term. Based on these outcomes, the study recommends that ECOWAS country authorities enhance policies to optimize government spending on infrastructure quality. Furthermore, adopting quality-enhancing and efficiency-driven financing policies in infrastructure is advocated to complement ECOWAS's ongoing infrastructural development efforts. The realization of these recommendations hinges on the availability of accurate data for informing decisions and guiding policymakers. Hence, the study underscores the need for the ECOWAS Commission to bolster its capacity for collecting reliable data on infrastructure variables and other indicators. It also proposes that future research should focus on promoting sub-regional peer-review mechanisms for infrastructure indicators among member states and establishing structures to fortify infrastructure in West Africa.